Case Report: Tachycardia, Hypoxemia and Shock in a Severely Burned Pediatric Patient - Shi, Jianshe; Huang, Chuheng; Zheng, Jialong; Ai, Yeqing; Liu, Hiufang; Pan, Zhiqiang; Chen, Jiahai; Shang, Runze; Zhang, Xinya; Dong, Shaoliang; Lin, Rongkai; Huang, Shurun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Severely burned children are at high risk of secondary intraabdominal hypertension and abdominal compartment syndrome (ACS). ACS is a life-threatening condition with high mortality and requires an effective, minimally invasive treatment to improve the prognosis when the condition is refractory to conventional therapy. Case presentation A 4.5-year-old girl was admitted to our hospital 30 h after a severe burn injury. Her symptoms of burn shock were relieved after fluid resuscitation. However, her bloating was aggravated, and ACS developed on Day 5, manifesting as tachycardia, hypoxemia, shock, and oliguria. Invasive mechanical ventilation, vasopressors, and percutaneous catheter drainage were applied in addition to medical treatments (such as gastrointestinal decompression, diuresis, sedation, and neuromuscular blockade). These treatments did not improve the patient's condition until she received continuous renal replacement therapy. Subsequently, her vital signs and laboratory data improved, which were accompanied by decreased intra-abdominal pressure, and she was discharged after nutrition support, antibiotic therapy, and skin grafting. Conclusion ACS can occur in severely burned children, leading to rapid deterioration of cardiopulmonary function. Patients who fail to respond to conventional medical management should be considered for continuous renal replacement therapy.